Label-Free Delineation of Human Uveal Melanoma Infiltration With Pump–Probe Microscopy - Zhang, Bohan; Yao, Tengteng; Chen, Yaxin; Wang, Chuqiao; Bao, Yongyang; Wang, Zhaoyang; Zhao, Keke; Ji, Minbiao (Frontiers in Oncology, 2022)
Uveal melanoma (UM) is the most frequent primary intraocular malignancy in adults, characterized by melanin depositions in melanocytes located in the uveal tract in the eyes. Differentiation of melanin species (eumelanin and pheomelanin) is crucial in the diagnosis and management of UM, yet it remains inaccessible for conventional histology. Here, we report that femtosecond time-resolved pump-probe microscopy could provide label-free and chemical specific detection of melanin species in human UM, based on their distinct transient relaxation dynamics at the sub-picosecond time scale. The method is capable of delineating the interface between melanoma and para-cancerous regions on various tissue conditions, including frozen sections, paraffin sections and fresh tissues. Moreover, transcriptome sequencing was conducted to confirmed the active eumelanin synthesis in UM. Our results may hold potentials for sensitive detection of tumor boundaries, as well as biomedical researches of melanin metabolism in UM.